"Embedded" assistance: Finn Church aid's secondment in Somalia - Rauli S. Lepistö; Rachel M. Gisselquist; Jussi Ojala (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Donors face distinct challenges in operating in fragile states and supporting the building of state capacity. This paper explores one type of assistance - the 'embedding' of highly-skilled staff members within local government agencies - through a unique case study of Finn Church Aid's experience with secondment in Somalia. Building upon FCA's previous work in Somalia, its staff member worked as part of the Transitional Federal Government's Ministry of Constitutional Affairs and Reconciliation to assist in the implementation of the roadmap designed to end transitional governance in the country. Although a number of such initiatives exist, few studies have explored how, why, and whether they work. Drawing on unique access to FCA staff and documents, as well as interviews with Somali stakeholders, donor representatives, and others, the paper explores FCA's experience and impact through this initiative, one way in which a non-state actor has provided tangible, relatively low cost support to a fragile state.
Keywords: F35; F51; H11; O22; 330; fragile states; foreign aid; peace-building; human rights-based approach; local ownership; Somalia